Text Criticism and Magical Performance of Wifq Musabbi’ in Ażimat Al-Haikal - Faqih Sulthan; Heri Dwi Santoso; Rijal Wakhid Rizkillah; Yunus Kholis Alhaqoni (SAWERIGADING, 2026)
This study aims to identify the dominant scribal characteristics and transcriptional errors affecting the readability of the text Ażimat al-Haikal, and to analyse the function of Qur’anic excerpts within the wifq musabbi’ sequence at the intersection of informational meaning and performative (talismanic) use. It employs a philological method using a standard edition approach, comprising transliteration, normalization, and minimal emendation, followed by a functional reception analysis. Data were collected through close examination of the sole manuscript preserved in the privately owned Baboh Haikal Pandahan collection (Tamansari, Jaken, Pati, Central Java), alongside the identification and classification of Qur’anic quotations from 32 surahs. Data analysis combines textual criticism to identify patterns of variation with reception analysis, drawing on Ibn Kathir’s tafsir to assess thematic correspondences and functional shifts. The findings reveal recurring variants, including addition, omission, dittography, substitution, and saut du même au même, indicating a permissive scribal culture that enables textual augmentation and recontextualization. Furthermore, reception analysis demonstrates partial thematic alignment between cited verses and their attributed functions (protection, healing, provision, and travel safety), while also revealing a shift from exegetical meaning toward pragmatic ritual purposes. This study contributes to Indonesian Islamic manuscript studies by providing a more accessible textual foundation and an analytical framework linking textual criticism with practical Qur’anic application. AbstrakPenelitian ini bertujuan untuk mengidentifikasi karakteristik penyalinan serta kesalahan transkripsi yang memengaruhi keterbacaan teks Ażimat Al-Haikal, serta menganalisis fungsi kutipan Al-Qur’an dalam rangkaian wifq musabbi’ pada pertemuan antara makna informasional dan peran performatif (talismanik). Metode yang digunakan adalah filologi dengan pendekatan edisi standar, yang mencakup transliterasi, normalisasi, dan emendasi minimal, dilanjutkan dengan analisis resepsi fungsional. Teknik pengumpulan data dilakukan melalui studi naskah tunggal yang tersimpan dalam koleksi privat Baboh Haikal Pandahan (Tamansari, Jaken, Pati, Jawa Tengah), serta identifikasi dan klasifikasi kutipan Al-Qur’an dari 32 surah. Teknik analisis data meliputi kritik teks untuk mengidentifikasi varian penyalinan, serta analisis resepsi untuk menelaah keterkaitan antara konteks ayat dan fungsi praktisnya dengan merujuk pada tafsir Ibn Kathir. Hasil penelitian menunjukkan adanya varian yang berulang, seperti penambahan, penghilangan, dittografi, substitusi, dan saut du même au même, yang mengindikasikan budaya penyalinan yang permisif dan memungkinkan terjadinya augmentasi serta rekontekstualisasi teks. Selain itu, resepsi pembaca menunjukkan adanya kesesuaian parsial antara tema ayat yang dikutip dengan fungsi yang dijanjikan (perlindungan, penyembuhan, kecukupan, dan keselamatan perjalanan), sekaligus memperlihatkan pergeseran dari pesan tafsir menuju tujuan ritual pragmatis. Penelitian ini memberikan kontribusi dalam studi naskah Islam di Indonesia melalui penyediaan landasan teks yang lebih terbaca serta kerangka analitis yang menghubungkan kritik teks dengan praktik penggunaan Al-Qur’an.